2005
DOI: 10.1159/000087516
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy of chromosome 18 in the baboon <i>(Papio hamadryas anubis)</i>

Abstract: Trisomy 18 is usually a lethal chromosomal abnormality and is the second most common autosomal trisomy in humans, with an incidence of 1:8000 live births. It is commonly associated with abnormalities of the lower and upper extremities, having the frequency of 95% and 65%, respectively. A newborn female olive baboon (Papio hamadryas anubis) was diagnosed with intrauterine growth retardation and severe arthrogryposis-like congenital joint deformities. Cytogenetic analysis including G-banding and fluorescence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Most assessed chromosomes in human preimplantation embryos are those commonly implicated in abnormal spontaneous abortions (chromosomes 13,16,18,21,22, X and Y) and chromosomally abnormal newborns (chromosomes 13, 18, 21, X and Y). Therefore, a comparable assay was developed for cytogenetic analysis of rhesus macaque preimplantation embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most assessed chromosomes in human preimplantation embryos are those commonly implicated in abnormal spontaneous abortions (chromosomes 13,16,18,21,22, X and Y) and chromosomally abnormal newborns (chromosomes 13, 18, 21, X and Y). Therefore, a comparable assay was developed for cytogenetic analysis of rhesus macaque preimplantation embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Human preimplantation embryos display a wide range of aneuploidies (36,42), however a smaller range is frequently observed in spontaneous abortions (frequently chromosomes 13,15,16,18,21,22, X and Y) or in newborns (commonly chromosomes 13, 18, 21, X and Y). This indicates that while all chromosomes are susceptible to segregation errors to a certain extent, only certain errors, like those generally assessed during PGD, are favorable to result in a clinical pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The most often recovered bacteria were Streptococcus spp. (17,29.8%), Staphylococcus spp. (16, 28.1%), Escherichia coli (11,19.3%), Pasteurella multocida (6, 10.5%), and Klebsiella pneumoniae (5, 8.8%); bacteria were identified histologically in seven baboons where lung culture was not performed.…”
Section: Morphologic Diagnosesmentioning
confidence: 99%
“…Infant necropsies (less than 2 days of age) during this period averaged 91 per year. One other autosomal abnormality (trisomy 18 in a baboon) has been identified in this time period [Howell et al, 2006]. Ruppenthal et al [2004] reported a case of trisomy 16 in a macaque and provided details of 11 previously reported cases of autosomal trisomy in nonhuman primates.…”
Section: Discussionmentioning
confidence: 91%